Inhibition of glycolate and D-lactate metabolism in a Chlamydomonas reinhardtii mutant deficient in mitochondrial respiration - Husic, Diane W. (1987)
The possibility that glycolate oxidation in unicellular green algae is linked to mitochondrial electron transport, rather than to peroxisomal metabolism as in higher plants and animals, was studied in a mutant of Chlamydomonas reinhardtii (dk97) deficient in cytochrome oxidase. This mutant had normal rates of dark respiration (40 ± 15 μmol of O(2) uptake per hr per mg of chlorophyll) but had only 11% of wild-type levels of cytochrome oxidase activity. Salicylhydroxamic acid (SHAM) reduced the dark respiration rate of dk97 cells by 71%, but cyanide did not significantly inhibit this rate. During photosynthesis in the presence of SHAM, glycolate oxidation was blocked, resulting in glycolate accumulation and excretion by mutant cells but not by wild-type Chlamydomonas. D-Lactate, which accumulated after brief periods of anaerobiosis in Chlamydomonas, was reoxidized by air-grown cells only aerobically in the light, and reoxidation of D-lactate was blocked by SHAM in the dk97 cells. Thus, glycolate and D-lactate dehydrogenase activities are both linked to mitochondrial electron transport in Chlamydomonas. During photosynthetic (14)CO(2) fixation by dk97 cells in the presence of SHAM, (14)C-labeled tricarboxylic acid cycle intermediates accumulated, indicating that, in Chlamydomonas, mitochondrial respiration functions during photosynthesis.